Transformational Leadership and Empathy: The Impact of Quality in the Health Care Services in Kelantan, Malaysia - Rahman, Wan Afezah Wan Abdul (International Journal of Economics, Business and Management Studies, 2017)
The study examined the relationship between transformational leadership, empathy and its impact on quality of health care services provided to the patients. The study used two types of questionnaires: a leadership inventory index (LPI) to measure the employees and the Consumer Assessment of Healthcare Providers and Systems (CAHPS) to measure the quality of services provided to the patients at Universiti Sains Malaysia Hospital, Malaysia. The results found that there is a significant relationship between transformational leaders and empathy, but there is no significant relationship between leadership effectiveness and service quality. The study found that the patients were satisfied with the quality of the services that they received at Universiti Sains Malaysia’s hospital.